Citation Analysis of Marketing Research: Key Contributions and Future Directions - , Vikash Chandra Gautam; , Arpita Sharma Kandpal; , Nisha Arya; , Sudhanand Prasad Lal (Archives of Current Research International, 2024)
Citation analysis measures the relative importance or impact of an author, article, or publication by counting the number of times other works have cited it. This research conducted a thorough examination within the marketing academic field, exploring the most cited articles and authors, the most published authors, publishing countries, universities, and the years with maximum contributions. The methodology involved selecting the top ten marketing journals based on the Scimago Journal and Country Rank (as of April 29, 2024). Data were collected from the Scopus database, encompassing 12,445 journal articles and 782,442 cited references. The results revealed Barry J. Babin as the most prolific author with 447 articles. The most cited article was "Uniting the Tribes: Using Text for Marketing Insight" with 772 citations. The United States led with 67,302 publications and 2,500,668 citations, while the University of Pennsylvania, Wharton School, had the highest number of publications at 235 articles. As of December 2019, Philip Kotler was identified as the most cited author in marketing, with 75,355 citations for his paper "Marketing Management: A South Asian Perspective" since 2009. This analysis provides valuable insights into the recent trends and future directions in the marketing field, highlighting significant contributions and influential works. However, the study's scope was limited to the top ten marketing journals from the SciMago list. Future research should consider a broader range of journals to gain a more comprehensive understanding of the marketing discipline.